Comprehensive characterization of potato TBL genes reveals candidates for salt and drought stress tolerance - Wang, Chenqi; Zhou, Xiaofeng; Wang, Bo; Qiao, Jianying; Xiong, Zhiyong; Wu, Lei (Frontiers in Plant Science, 2026)
The Trichome Birefringence-Like (TBL) gene family encodes polysaccharide acetyltransferases that modify polysaccharide properties, playing key roles in trichome development, cell wall acetylation, and responses to biotic and abiotic stresses. Potato, a globally important crop, frequently faces salinity and drought stress. However, the role of the potato TBL gene family in stress resistance remains unexplored. Using bioinformatics, we identified 72 StTBL genes in the potato DM1-3–516 R44 genome, unevenly distributed across 12 chromosomes. Phylogenetic analysis grouped them into three subfamilies with conserved domains including PC-Esterase, PMR5N, and DUF4283. We further examined gene structure, promoter cis-elements, predicted miRNA targets, GO annotations, and tissue-specific expression. Under both salt and drought stress, we identified several responsive candidate genes from the 72 StTBLs: 10 potential salt-responsive candidates (StTBL 1, StTBL 3, StTBL 16, StTBL 20, StTBL 22, StTBL28, StTBL 58, StTBL 59, StTBL 60 and StTBL 68) and 11 potential drought-responsive candidates (StTBL 1, StTBL 2, StTBL 3, StTBL 12, StTBL 19, StTBL 21, StTBL 22, StTBL 28, StTBL31, StTBL 33 and StTBL 69). This study presents the first genome-wide characterization of the TBL gene family in potato. The findings highlight candidate genes for improving salt and drought tolerance, offering insights for developing stress-resilient potato.